2021
DOI: 10.2147/idr.s300162
|View full text |Cite
|
Sign up to set email alerts
|

BCG Vaccine-Induced Trained Immunity and COVID-19: Protective or Bystander?

Abstract: In late 2019, a new virulent coronavirus (CoV) emerged in Wuhan, China and was named as severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). This virus spread rapidly, causing the coronavirus disease-2019 (COVID-19) pandemic. Bacillus Calmette-Guérin (BCG) is a live attenuated tuberculosis (TB) vaccine, associated with induction of non-specific cross-protection against unrelated infections. This protection is a memory-like response in innate immune cells (trained immunity), which is caused by epigenet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 123 publications
0
11
0
Order By: Relevance
“…Two recent review articles provided an effective overview of current literature and understanding of BCG and COVID-19. 13 , 14 They review early epidemiological studies, as well as provide an overview of ongoing clinical trials, and importantly conclude that the results of these ongoing clinical trials will be important in confirming data from ecological studies and small observational studies such as this one. Trained immunity induced by vaccines such as BCG may be an important bridge before more widespread availability of specific vaccines, possibly an effective adjunct alongside specific vaccines, and likely an important tool in future viral pandemics.…”
mentioning
confidence: 99%
“…Two recent review articles provided an effective overview of current literature and understanding of BCG and COVID-19. 13 , 14 They review early epidemiological studies, as well as provide an overview of ongoing clinical trials, and importantly conclude that the results of these ongoing clinical trials will be important in confirming data from ecological studies and small observational studies such as this one. Trained immunity induced by vaccines such as BCG may be an important bridge before more widespread availability of specific vaccines, possibly an effective adjunct alongside specific vaccines, and likely an important tool in future viral pandemics.…”
mentioning
confidence: 99%
“…Reports showed that nations with mandatory BCG vaccination had fewer numbers of patients with COVID-19. 20 22 Therefore, induction of trained immunity through BCG vaccination was thought to be a potentially effective approach to protect against SARS-CoV-2 infection. 20–24 We did not observe any association between COVID-19 infection and BCG vaccination.…”
Section: Discussionmentioning
confidence: 99%
“… 20 22 Therefore, induction of trained immunity through BCG vaccination was thought to be a potentially effective approach to protect against SARS-CoV-2 infection. 20–24 We did not observe any association between COVID-19 infection and BCG vaccination. BCG vaccination coverage is high in Bangladesh and we observed that 82% of both the COVID-19 positives and negatives had BCG scars in the upper arm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BCG vaccination may modulate antiinflammatory cytokine and chemokine responses, resulting in fewer hospitalizations and lesser COVID-19 events. According to studies, countries that use BCG in their national vaccination programs (BCG countries) have fewer reported COVID-19 cases per million people than countries that do not use BCG [ 57 ]. In addition to the effect of BCG vaccinated to be associated a decrease in the incidence of sickness during the COVID-19 pandemic, co-administration of BCG and SARS-CoV-2 vaccines may have synergistic protective effects, including increased efficacy and/or duration of the memory response [ 58 ].…”
Section: Vaccinesmentioning
confidence: 99%